7x-2=4x-2

Simple and best practice solution for 7x-2=4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2=4x-2 equation:


Simplifying
7x + -2 = 4x + -2

Reorder the terms:
-2 + 7x = 4x + -2

Reorder the terms:
-2 + 7x = -2 + 4x

Add '2' to each side of the equation.
-2 + 2 + 7x = -2 + 2 + 4x

Combine like terms: -2 + 2 = 0
0 + 7x = -2 + 2 + 4x
7x = -2 + 2 + 4x

Combine like terms: -2 + 2 = 0
7x = 0 + 4x
7x = 4x

Solving
7x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
7x + -4x = 4x + -4x

Combine like terms: 7x + -4x = 3x
3x = 4x + -4x

Combine like terms: 4x + -4x = 0
3x = 0

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 | | 5x+45-89=-90+41 | | 3+2p=7 | | -5(2(2)+7)+2(9)+5(-5)= | | 5(z-1)-20=0 | | Y=2ln(3x-1)-2 | | -10x^2-6x-12=0 | | -4=-8x+2 | | 9(4(-25)-3)= | | ln(x-6)=24 | | 90t=450t | | 9t^2-54=0 | | -24r+6= | | 9(-5)(2)+3(-25)-7(4)+8(-5)(2)-12= | | Y=-8sin(7x) | | 8=2d-12 | | -7x-y+z=-12 | | x-9=.75x | | (5x+5)+(-6x+8)= | | x^2+y^2+18x+12y=11 | | 8b+3=5b+7 | | 3(3x-7)=81(12x-3x) | | 2/12= | | e^7x=10 | | -7(3(-5)-4)+2= | | -4(3(-5)-5(2)-7)= | | 2-2x-6x=26 | | 5r^3+r^2=80r+16 | | 2h-1=1 | | 5(2(-5)+6)-12(-5)= |

Equations solver categories